2016
DOI: 10.1111/pbi.12602
|View full text |Cite
|
Sign up to set email alerts
|

Reduced paucimannosidic N‐glycan formation by suppression of a specific β‐hexosaminidase from Nicotiana benthamiana

Abstract: SummaryPlants are attractive hosts for the production of recombinant glycoproteins for therapeutic use. Recent advances in glyco‐engineering facilitate the elimination of nonmammalian‐type glycosylation and introduction of missing pathways for customized N‐glycan formation. However, some therapeutically relevant recombinant glycoproteins exhibit unwanted truncated (paucimannosidic) N‐glycans that lack GlcNAc residues at the nonreducing terminal end. These paucimannosidic N‐glycans increase product heterogeneit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 43 publications
(83 reference statements)
4
64
0
Order By: Relevance
“…This correlates with a recent study (Shin et al, 2016) that demonstrated that in N. benthamiana , the presence of the core α(1,3)-fucose on the N -glycans enhances the trimming of GlcNAc residues. These authors showed that this trimming is due to the activity of β-hexosaminidases, mainly located in the plasma membrane in leaf epidermal cells.…”
Section: Discussionsupporting
confidence: 91%
“…This correlates with a recent study (Shin et al, 2016) that demonstrated that in N. benthamiana , the presence of the core α(1,3)-fucose on the N -glycans enhances the trimming of GlcNAc residues. These authors showed that this trimming is due to the activity of β-hexosaminidases, mainly located in the plasma membrane in leaf epidermal cells.…”
Section: Discussionsupporting
confidence: 91%
“…The absence of these sugar residues from the endogenous N-glycans of the FX-KO line thus results in less trimming and consequently a higher content of GnGn. For the 2G12 glycovariants, on the other hand, the main glycoforms were GnGn(F/X) variants in all tested samples (Table 3) as was the case for the 2G12 glycovariants expressed in the RNAi N. benthamiana lines by Strasser et al (2008), likely because the antibody heavy chain is not a substrate for the bhexosaminidases present in the cell (Shin et al, 2017).…”
Section: Discussionmentioning
confidence: 78%
“…For the 2G12 glycovariants, on the other hand, the main glycoforms were GnGn(F/X) variants in all tested samples (Table ) as was the case for the 2G12 glycovariants expressed in the RNAi N. benthamiana lines by Strasser et al . (), likely because the antibody heavy chain is not a substrate for the β‐hexosaminidases present in the cell (Shin et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Unlike in humans and higher organisms in which paucimannosylation is now being considered as an immunecentric N-glycan type (Loke et al, 2016) important for cellcell immune communication, for fighting pathogenic infections and for the proliferation of neural progenitor cells (Dahmen et al, 2015;Thaysen-Andersen et al, 2015), it has been established that plants constitutively and abundantly express plant-specific paucimannosidic N-glycan structures (Man 1-3 Xyl 0-1 Fuc 0-1 GlcNAc 2 ) as a common part of their glycoprotein repertoire (Dam et al, 2013;Shin et al, 2017). Trimming of GlcNAc caps of the developing complex/hybrid N-glycan intermediates to paucimannosidic structures is catalysed by the hexosaminidases (HEXO I, II, and III) localised in the plasma or vacuole membranes.…”
Section: Introductionmentioning
confidence: 99%